2020
DOI: 10.1063/1.5143351
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical study on the attenuation effect on the blast wave of encircling a high explosive with granular media

Abstract: This study explored the practicality of a two-phase flow model for granular media in elucidating the attenuation mechanism of the blast wave. To validate the model, the numerical data were compared with the results of the previous experiments in terms of the interaction between the planar shock wave and particle layer, dispersal of steel particles saturated with a liquid explosive after the detonation of the explosive, and attenuation effect of the particle layer on the blast wave. Results of the validation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…This method was used by Sugiyama et al. (2020, 2021) and McGrath, Clair & Balachandar (2016). The drag factor is given as where and with defining the relative Reynolds number with air viscosity as …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This method was used by Sugiyama et al. (2020, 2021) and McGrath, Clair & Balachandar (2016). The drag factor is given as where and with defining the relative Reynolds number with air viscosity as …”
Section: Methodsmentioning
confidence: 99%
“…2018 a , b ; Sugiyama et al. 2020) to encircle the high explosive. These studies have confirmed significant reductions in the peak overpressure and positive impulse.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of reactive particles to enhance explosive blasts, increase quasistatic overpressure, and produce extended energy release through afterburning processes is an active research topic [1][2][3][4][5][6][7][8][9][10][11]. The detonation of a condensed phase explosive, which may contain energetic particles, is a precursor event to particle dispersal, turbulent mixing, and afterburning processes [12].…”
Section: Introductionmentioning
confidence: 99%